Beyond Digital Payments: the Role of Financial Literacy and Social Preferences in Shaping Financial Self-Control - Heni Subekti; Infijarun Ni'am; Wachidah Fauziyanti (Asian Journal of Management Analytics, 2026)
This study aims to analyze the influence of financial literacy on financial self-control by considering the mediating role of social preference and digital wallet. This study uses a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data was collected through a questionnaire distributed to 160 respondents and analyzed to test the relationship between variables. The results of the study show that financial literacy has a positive and significant effect on social preference and digital payment use. Social preference and digital wallet also have a significant effect on financial self-control. The mediation analysis shows that social preference plays a stronger role as a mediator in the relationship between financial literacy and financial self-control compared to digital payment use. These findings indicate that financial self-control is not only influenced by cognitive and technological aspects, but is also highly determined by social dimensions.